2018
DOI: 10.1371/journal.pone.0193697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mental health screening tools for detecting antenatal depression and anxiety disorders in South African women

Abstract: BackgroundAntenatal depression and anxiety disorders are highly prevalent in low and middle-income countries. Screening of pregnant women in primary care antenatal settings provides an opportunity for entry to care, but data are needed on the performance of different screening tools. We compared five widely-used questionnaires in a sample of pregnant women in urban South Africa.MethodPregnant women attending a primary care antenatal clinic were administered five tools by trained research assistants: the Edinbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 56 publications
3
51
0
1
Order By: Relevance
“…2018). We used these results as a starting point to conduct the primary logistic regression to identify screening items that were independently predictive of MDE and anxiety diagnoses (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2018). We used these results as a starting point to conduct the primary logistic regression to identify screening items that were independently predictive of MDE and anxiety diagnoses (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A high level of sensitivity in a screening tool is important for first-level screening purposes, however in resource-constrained areas this needs to be balanced with adequate specificity so as not to flood the system with false positives. The sensitivity (78%) and specificity (82%) of our tool in detecting MDE and anxiety disorders seems favourable compared to the EPDS (75%; 78%) and the PHQ9 (66%; 76%), as well as ultra-short versions of these: the 3-item EPDS (70%; 77%), the PHQ2 (75%; 69%) and the Whooley questions (66%; 87%) (van Heyningen et al 2018). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies addressing structural factors showed promising results with integration of postpartum care into routine care for the child or family [66] [67], mHealth reminders and cash transfers [68][69][70][71][72]. Ongoing studies will evaluate effects of mHealth strategies [73,74], reaching women with mental health challenges in pregnancy and postpartum [75,76] and adherence clubs/decentralized care [77]. Women in different contexts will require different types of support [78,79] and an adaptive trial design [80] may be an efficient way to evaluate strategies to combine intervention elements to support women to remain in care [81].…”
Section: Discussionmentioning
confidence: 99%
“…The EPDS is a ten-question self-rating scale developed to assess depressive symptoms in the postnatal period [32]. This scale can also be used to identify depression in the antenatal period [33][34][35]. On the EPDS, respondents are asked to identify the answer that most closely represents how they felt in the previous seven days.…”
Section: Overview Of the Food Feelings And Family Studymentioning
confidence: 99%